Difficulties Facing English Foreign Language University Students in Using English Prepositions - Fathi, Kadija (مجلة كلية الاداب, 2024)
Prepositions are one of the most used parts of speech in English. This study is concerned with the difficulties are facing Libyan higher education students on the use of English prepositions. More specifically, this study is an attempt to discover these problems and the misuse of these prepositions. This study is a quantitative. Seventy-six EFL students were randomly selected from Libyan English department in Faculty of Education. The objective test was the main instrument for data collection. The results showed that Libyan students committed varied kinds of the errors in the use of prepositions. Analysis of the responses revealed that errors made were mainly based on the function and replacement of the prepositions. The difficulties encountered in the use of prepositions are linked to the nature of English prepositions: polysemy, idiomatic usage and substitution with first language prepositions. Another strategy to teaching English prepositions is required to improve students’ performance.